Class Ib Ribonucleotide Reductases: Activation of a Peroxido-MnIIMnIII to Generate a Reactive Oxo-MnIIIMnIV Oxidant - Mc Donald, Aidan (My University, 2024)
In the postulated catalytic cycle of class Ib Mn2 ribonucleotide reductases (RNRs), a MnII2 core is suggested to react with superoxide (O2·-) to generate peroxido-MnIIMnIII and oxo-MnIIIMnIV entities prior to proton-coupled electron transfer (PCET) oxidation of tyrosine. There is limited experimental support for this mechanism. We demonstrate that [MnII2(BPMP)(OAc)2](ClO4) (1, HBPMP = 2,6-bis[(bis(2 pyridylmethyl)amino)methyl]-4-methylphenol) was converted to peroxido-MnIIMnIII (2) in the presence of superoxide anion that converted to (μ-O)(μ-OH)MnIIIMnIV (3) via the addition of an H+-donor (p-TsOH) or (μ-O)2MnIIIMnIV (4) upon warming to room temperature. The physical properties of 3 and 4 were probed using UV-vis, EPR, X-ray absorption, and IR spectroscopies and mass spectrometry. Compounds 3 and 4 were capable of phenol oxidation to yield a phenoxyl radical via a concerted PCET oxidation, supporting the proposed mechanism of tyrosyl radical cofactor generation in RNRs. The synthetic models demonstrate that the postulated O2/Mn2/tyrosine activation mechanism in class Ib Mn2 RNRs is plausible and provides spectral insights into intermediates currently elusive in the native enzyme
PUBLISHED
Keywords: Mn2 ribonucleotide reductases; proton-coupled electron transfer (PCET); native enzyme